Global Burden of Childhood Epilepsy, Intellectual Disability, and Sensory Impairments - Olusanya, Bolajoko O.; Wright, Scott M.; Kuper, Hannah; Abubakar, Amina A.; Kakooza-Mwesige, Angelina; Kassebaum, Nicholas J. (Pediatrics, 2020)
Estimates of children and adolescents with disabilities worldwide are needed to inform global intervention under the disability-inclusive provisions of the Sustainable Development Goals. We sought to update the most widely reported estimate of 93 million children <15 years with disabilities from the Global Burden of Disease Study 2004.